An Ab Initio Parameterization of the DFT/MRCI Method for Valence and Core Excitation - Costain, Teagan (Université d'Ottawa / University of Ottawa, 2025)
With the latest technological advancements related to spectroscopy, experimental capabilities have become ever more sophisticated. Theoreticians must therefore meet ever-growing demands to analyze the experimental data in time-resolved studies of ultrafast molecular dynamics. An indispensable tool in the theoretician's toolbox is electronic structure theory, the study of methods to describe electronic wave functions. With a focus on the combined density functional theory and multi-reference configuration interaction (DFT/MRCI) method, this thesis aims to highlight the importance of developing semi-empirical methods to achieve balance between the predictive accuracy of purely ab initio methodology and the computational efficiency of empirical methodology. To this end, this thesis presents two new parameterizations of the DFT/MRCI method for valence and core-excited states that, respectively, achieve sub-eV error metrics with respect to benchmark vertical excitation energies.
Keywords: Quantum Chemistry; Physical Chemistry; Electronic Structure Theory